Música em fluxo : transformações na indústria fonográfica a partir do streaming - Silva Júnior, Flávio Marcílio Maia e (2018)
With the popularization of streaming in the music industry, new actors and models of production emerge and strengthen the idea of excluding world record companies from stages such as recording and distribution of music. This research analyzes two musical joints related to streaming that consolidate the hypothesis of weakening of these companies: the production of songs made by Spotify and the intermediation of the aggregating companies in the distribution of digital music. However, major record companies, also known as majors, still hold a hegemonic position and seek alternatives to remain profitable in this environment. On other hand, the insertion of streaming into the production chain of music is a phenomenon in development that serves the majors and artists considered independent. To understand the growth of streaming as a trend for the consumption of music on the Internet, it was necessary to carry out a literature review and an analysis of the reports and documents published by Pro-Música Brasil in the last ten years. Interviews with music professionals were also conducted with the objective of identifying new relationships with music in the digital scene.